2021
DOI: 10.1002/ccd.29701
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes of self‐expanding versus balloon‐expandable transcatheter aortic valves: Insights from the OBSERVANT study

Abstract: Objectives: To compare clinical outcomes of balloon-expandable (BE) and selfexpanding (SE) transcatheter aortic valves (TAVs) up to 5 years. Background:To date, no robust, comparative data of BE and SE TAVs at long-term are available.Methods: We considered a total of 1,440 patients enrolled in the multicenter OBSERVANT study and undergoing transfemoral transcatheter aortic valve implantation (TF-TAVI) with either supra-annular SE (n = 830, 57.6%) and intra-annular BE (n = 610, 42.4%) valves. Clinical outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Although this does not impact on early outcomes and bioprosthesis functioning, comparison of these devices in larger dataset with longer follow-up is needed for a proper evaluation of the eventual clinical relevance of this finding. 22 Unfortunately, the OBSERVANT II study did not provide echocardiographic follow-up of TAVI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Although this does not impact on early outcomes and bioprosthesis functioning, comparison of these devices in larger dataset with longer follow-up is needed for a proper evaluation of the eventual clinical relevance of this finding. 22 Unfortunately, the OBSERVANT II study did not provide echocardiographic follow-up of TAVI patients.…”
Section: Discussionmentioning
confidence: 99%
“…Overall: A total of twenty-one studies 7 16 , 18 , 19 , 21 23 , 25 29 , 31 , 32 were included that assessed mortality. Our analysis found that the results were significant for BEV compared to SEV for overall mortality.…”
Section: Resultsmentioning
confidence: 99%
“…Moderate or severe PVR is associated with increased risk of death and heart failure rehospitalizations. Although the incidence of moderate or even severe PVR has declined considerably with the use of second-generation TAVI devices [25], there is evidence that mild PVR, which is still present in a sizable portion of patients, might negatively affect longterm survival as well [1][2][3] and should be avoided in a lowrisk population, in which surgical aortic valve replacement is a viable alternative.…”
Section: Rationalementioning
confidence: 99%
“…Paravalvular regurgitation (PVR) remains an important drawback of transcatheter aortic valve implantation (TAVI) with negative prognostic implications for the patient [1][2][3]. Apart from procedural causes, its incidence depends on sealing zone anatomy, quantified for example by measures of calcium protrusion into the lumen [4], semiquantitatively graded calcium bulks [5] or landing zone eccentricity or nontubularity [6,7].…”
Section: Introductionmentioning
confidence: 99%